Los indignados del 15-M. Nuevas formas de resistencia ciudadana (2012)
ABSTRACT: This work, developed in Madrid and Barcelona, explores new forms of protests by 15-M indignant people. From the perspective of social subjects, we can see how people reactand use resources to protest against the control and domination of fiance capital and government, as there reduce the historic achievements of the welfare state.